PENGARUH MOTIVASI TERHADAP PRESTASI BELAJAR IPA SISWA KELAS VIII SMP SWASTA TAMAN ILMU PERLANAAN KECAMATAN BANDAR SIMALUNGUN TAHUN PELAJARAN 2019/2020 - Rolinca Siburian, Juliana; Wilson Sitopu, Joni (Jurnal Metabio, 2021)
This study was conducted with the aim of determining the Effect of Motivation on Science Learning Achievement of Grade VIII Students of Taman Ilmu Perlanaan Private Junior High School, Bandar Simalungun District, Academic Year 2019/2020. The number of samples in this study is the same as the population with a total of 52 people consisting of 2 classes. The research instrument used to collect data was a questionnaire about Learning Motivation variable (X) and a mid-semester Value Collection List (DKN) to determine science learning achievement (Y variable). From the hypothesis testing obtained t count > Sig. (2-tailed), (2.694> 0.010) then Ha is accepted and Ho is rejected which means there is a very significant influence between Motivation on Science Learning Achievement of Grade VIII Students of Taman Ilmu Perlanaan Private Junior High School, Bandar Simalungun District, Academic Year 2019/2020. The results of the regression analysis obtained a linear regression equation: Ŷ = 86.411 X + 0.057. The equation shows that students' science learning achievement is influenced by motivation. The following conclusions are drawn: 1) There is a positive influence of motivation on science learning achievement, which is acceptable. 2) Based on a simple linear regression analysis (F test), the calculated F (0.230) > Fsig. (0.0633) can be obtained. It can be concluded that the linear regression direction coefficient is significant with a correlation coefficient contribution of  0.068, so the determination coefficient is 4.6%, a very low correlation.